Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan pada Daerah Tertinggal di Pulau Sumatera Berdasarkan Tipologi Klassen - Niken Ayudia; Ukhti Ciptawaty; Heru Wahyudi; Dedy Yuliawan; Arivina Ratih (Journal on Education, 2024)
Poverty is a state of being unable to meet fundamental necessities. This study seeks to examine districts that are classified as disadvantaged areas based on the classen typology and analyse the factors that impact the extent of poverty in these regions. The classen typology employs secondary data consisting of the rate of economic growth and per capita income. This dataset includes information on 154 districts in Sumatra from 2015 to 2022. It examines the elements that contribute to poverty, such as RLS data, GRDP per capita, TPT, and poverty levels in 46 districts classified as undeveloped according to the classen typology during the same period. The research use classen typology and panel data regression as analytical techniques. According to the classen typology, the results indicate that there are 46 districts classified as relatively underdeveloped areas. The implementation of TPT has a beneficial impact on alleviating poverty in impoverished regions on the island of Sumatra. Conversely, GRDP per capita and RLS exhibit a detrimental impact. The combination of these three elements together impacts poverty.